Some Constraints for Models of Timing: A Temporal Coding Hypothesis Perspective - Arcediano, Francisco; Miller, Ralph R. (Learning and motivation, 2002)
Most contemporary models of timing in animals were developed to account for the measurement of temporal intervals as they increase. Here we review growing evidence of timing in backward conditioning, which suggests that subjects exposed to Stimulus S1 followed by Stimulus S2 store information allowing the representation of S2 to retrieve both the occurrence and specific temporal location of S1. Such phenomena provide new and challenging constraints for models of timing.